Creation of a tweezer array for cold atoms utilizing a generative neural network - Zejian Ren; Xu Yan; Kai Wen; Huijin Chen; Elnur Hajiyev; Chengdong He; Gyu-Boong Jo (APL Quantum)
Optical tweezers have become an essential tool for dynamically manipulating objects, ranging from microspheres or biological molecules to neutral atoms. In this study, we demonstrate the creation of tweezer arrays using a generative neural network, which allows the trapping of neutral atoms with tunable atom arrays. We have successfully loaded cold strontium atoms into various optical tweezer patterns generated using a spatial light modulator (SLM) integrated with generative models. Our approach shortens the process time to control the SLM with a minimal time delay, eliminating the need for repeated re-optimization of the hologram for the SLM.